Electronic word of mouth about medical services - Vera Hinz; Florian Drevs; Jürgen Wehner (University of Hamburg, Hamburg Center for Health Economics (HCHE), 2012)
Electronic word of mouth (eWOM) about medical services gains growing popularity from the part of health care users, accompanied with a high reluctance of health care providers towards existing platforms, fearing unqualified, negative reviews driven by motives of vengeance. Purpose of this research is to shed light on the characteristics, content, and motives of eWOM about medical services. Using primary and secondary data of 822 reviews, this study shows that reviews about medical services are positive more often than negative, and that altruistic motives override egoistic motives. Furthermore, why a review is written significantly relates to the review's valence (positive, negative), degree of affectivity, and degree of differentiation. Motives and characteristics also affect the review's content, differentiated in four aspects (medical care, relationships, comfort, and processes). Hence this study counters the arguments of many health care providers and offers new insights in an underresearched field, providing implications for both management and future research.
Keywords: 330; Electronic word of mouth; online reviews; health care management; hospitals; Virales Marketing; Internet; Gesundheitswesen